(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Dependence of conductivity on temperature of sodium bis(2-ethylhexyl) sulfosuccinate (AOT)–n-heptane–water+dimethylsulfoxide (DMSO) or diethylsulfoxide (DESO) reverse micellar system has been studied at fixed ratio of molal concentrations of polar phase (water, water+DMSO, water+DESO) to surfactant and at different volume ratios of DMSO (DESO) and water. The threshold percolation temperatures (Tp) for each system have been estimated, the effects of both DMSO and DESO on threshold percolation temperature and percolation process have been discussed. Both DMSO and DESO act as percolation-resisting additives. The presence of mixed solvent has shown a decrease of Tp and tendency to transfer a system from percolating to non-percolating. The activation energy (Ep) for percolation of conductance has also been determined according to Arrhenius equation. The results show that Ep decreases with addition of DMSO or DESO and with an increase of concentration of DMSO.